2021
DOI: 10.1021/acs.estlett.1c00291
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Reveals Vulnerabilities of the Food–Energy–Water Nexus to Viral Pandemics

Abstract: Food, energy, and water (FEW) sectors are inextricably linked, making one sector vulnerable to disruptions in another. Interactions between FEW systems, viral pandemics, and human health have not been widely studied. We mined scientific and news/media articles for causal relations among FEW and COVID-19 variables and qualitatively characterized system dynamics. Food systems promoted the emergence and spread of COVID-19, leading to illness and death. Major supply-side breakdowns were avoided (likely due to low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 82 publications
(117 reference statements)
0
19
0
Order By: Relevance
“…Ten papers investigated the disruptions and uncertainties to the supply chain caused by the COVID‐19 pandemic (Achmad et al, 2021 ; Burgos & Ivanov, 2021 ; Choudhary et al, 2021 ; Duan et al, 2021 ; Ghadge et al, 2021 ; Moosavi & Hosseini, 2021 ; Nguyen, 2021 ; Sinha et al, 2020 ) and the post‐pandemic recovery strategies (Ivanov, 2021 ; Rahman et al, 2021 ). Twenty papers explored the other sectors at the national and regional levels, including industrial network (Song et al, 2020 ), tourism (Gu et al, 2021 ; Luo et al, 2021 ), national security (Prikazchikov et al, 2021 ), food–energy–water (Calder et al, 2021 ), economy (Chen et al, 2021 ; Fosco & Zurita, 2021 ; Inoue et al, 2021 ; Inoue & Todo, 2020 ; Sharma et al, 2021 ), financial (Spelta et al, 2021 ), social activity (de Brito Jr et al, 2021 ; Schmidt & Albert, 2021 ; Weibrecht et al, 2021 ), healthcare (Schlüter et al, 2021 ), employment (Marreros et al, 2021 ) and transport and land‐use (Habib & Anik, 2021 ). As the pandemic led to great collateral damage or process disruption to a variety of organizations, including banks (Shahabi et al, 2021 ), airlines (Delcea et al, 2020 ; Milne et al, 2020 , 2021 ), ambulatory endoscopy centres (Das, 2020 ), heart clinics (Zeinalnezhad et al, 2020 ), laboratories (Lim et al, 2020 ) and outpatient dialysis services (Allen, Bhanji, et al, 2020 ), necessary countermeasures were adopted to lower the risk of transmission and to improve effectiveness of these measures.…”
Section: Resultsmentioning
confidence: 99%
“…Ten papers investigated the disruptions and uncertainties to the supply chain caused by the COVID‐19 pandemic (Achmad et al, 2021 ; Burgos & Ivanov, 2021 ; Choudhary et al, 2021 ; Duan et al, 2021 ; Ghadge et al, 2021 ; Moosavi & Hosseini, 2021 ; Nguyen, 2021 ; Sinha et al, 2020 ) and the post‐pandemic recovery strategies (Ivanov, 2021 ; Rahman et al, 2021 ). Twenty papers explored the other sectors at the national and regional levels, including industrial network (Song et al, 2020 ), tourism (Gu et al, 2021 ; Luo et al, 2021 ), national security (Prikazchikov et al, 2021 ), food–energy–water (Calder et al, 2021 ), economy (Chen et al, 2021 ; Fosco & Zurita, 2021 ; Inoue et al, 2021 ; Inoue & Todo, 2020 ; Sharma et al, 2021 ), financial (Spelta et al, 2021 ), social activity (de Brito Jr et al, 2021 ; Schmidt & Albert, 2021 ; Weibrecht et al, 2021 ), healthcare (Schlüter et al, 2021 ), employment (Marreros et al, 2021 ) and transport and land‐use (Habib & Anik, 2021 ). As the pandemic led to great collateral damage or process disruption to a variety of organizations, including banks (Shahabi et al, 2021 ), airlines (Delcea et al, 2020 ; Milne et al, 2020 , 2021 ), ambulatory endoscopy centres (Das, 2020 ), heart clinics (Zeinalnezhad et al, 2020 ), laboratories (Lim et al, 2020 ) and outpatient dialysis services (Allen, Bhanji, et al, 2020 ), necessary countermeasures were adopted to lower the risk of transmission and to improve effectiveness of these measures.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic has shown us that the interactions between WEF systems, viral pandemics, and human health have not been extensively studied as there is practically no quantitative analysis of any of these compensations or feedbacks (Calder et al, 2021 ). However, it is also revealed that WEF interconnections are not only vulnerable to resource constraints, but also to disruptions in human and financial capital on the supply and demand side (Al-Saidi & Hussein, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since attempts to stop the spread of the virus have resulted in widespread economic and social disruption. Supply-side shocks have been characterized as having to do with the disruption of labor inputs and mismatches in the size of food packages caused by the closure of restaurants and other food services (Calder et al, 2021 ); however, we also consider disruptions in the logistics of products, which can be internal (displacement of producers and intermediaries, interruptions in national roads) or external, which can disrupt international trade supply chains through border road blockades or closures of ports and airports, as well as delays in customs. In addition, the volatility of internal prices and external policies that restrict exports, which can be tariff or sanitary, are considered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The infant formula shortage was caused in part by voluntary recalls of several formulas produced by Abbott Nutrition, shutdown of an Abbott Nutrition plant in Michigan in February 2022 due to bacterial contamination, 2 and ongoing supply chain interruptions resulting from the COVID-19 pandemic. 3 Because Abbott is among the largest suppliers of infant formula in the US, and produces specialized formulas for infants with severe allergies, gastrointestinal conditions, and metabolic disorders, 4 access to specialized formulas rapidly diminished early in 2022. This resulted in a lack of appropriate nutrition for infants with these and other health conditions.…”
Section: Introductionmentioning
confidence: 99%